2017
DOI: 10.3945/ajcn.117.156877
|View full text |Cite
|
Sign up to set email alerts
|

Association between noncow milk beverage consumption and childhood height

Abstract: Background: Cow milk consumption in childhood has been associated with increased height, which is an important measure of children's growth and development. Many parents are choosing noncow milk beverages such as soy and almond milk because of perceived health benefits. However, noncow milk contains less protein and fat than cow milk and may not have the same effect on height. Objective: We sought to determine whether there is an association between noncow milk consumption and lower height in childhood and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
0
32
0
3
Order By: Relevance
“…At 12 weeks postnatal, infants receiving a high sn-2 palmitate formula (i.e., mimicking the sn-2 palmitate content of human milk) since birth had significantly greater absorption of fat and calcium, and higher bone strength compared to infants receiving a regular formula with low sn-2 palmitate [38]. Approximately 40% to 60% of adult bone mass accrues during adolescence and milk intake during childhood and adolescence has been associated with higher BMC, with consumption of more than three servings of milk per day associated with a greater adult height in girls compared to those drinking less than one serving per day [31]. For each cup of plant-based drink relative to milk, children were 0.4 cm (95% CI 0.2-0.8 cm) shorter.…”
Section: The Dairy Food Matrix and Plant-based Alternatives In Relatimentioning
confidence: 98%
See 1 more Smart Citation
“…At 12 weeks postnatal, infants receiving a high sn-2 palmitate formula (i.e., mimicking the sn-2 palmitate content of human milk) since birth had significantly greater absorption of fat and calcium, and higher bone strength compared to infants receiving a regular formula with low sn-2 palmitate [38]. Approximately 40% to 60% of adult bone mass accrues during adolescence and milk intake during childhood and adolescence has been associated with higher BMC, with consumption of more than three servings of milk per day associated with a greater adult height in girls compared to those drinking less than one serving per day [31]. For each cup of plant-based drink relative to milk, children were 0.4 cm (95% CI 0.2-0.8 cm) shorter.…”
Section: The Dairy Food Matrix and Plant-based Alternatives In Relatimentioning
confidence: 98%
“…These are often presented as suitable alternatives to milk, though nutritionally their content may not compare at all, especially for products essentially devoid of protein ( Table 1). The small number of prospective studies and RCTs comparing dairy products with plant-based alternatives indicate that dairy appears more beneficial for bone health [31,32].…”
Section: The Dairy Food Matrix and Plant-based Alternatives In Relatimentioning
confidence: 99%
“…In most developed countries, over two-thirds of calcium consumption originates from milk products [18] and avoiding milk exposes children to the risk of low calcium levels and restricted growth. A recent study showed that each daily cup of cow's milk was associated with 0.2 centimeters additional height compared to non-cow's milk consumption in 3-year-old children [19]. Another study reported that consuming dairy products during childhood improved bone density in adulthood, and that their avoidance may lead to growth deceleration and osteoporosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike genetically specified traits, environmental factors that begin during gestation also play a significant role in determining adult height. In this issue of the Journal, Morency et al (6) provide an example of an association between diet (environment) and childhood height in the TARGet Kids Collaboration study. With the use of a cross-sectional approach, the authors show a dose-dependent association between higher noncow-milk consumption and lower height in 5034 children.…”
mentioning
confidence: 99%
“…Morency et al (6) and Ma et al (8) should be commended for their contributions to this subject. So, should we encourage more noncow-milk consumption in childhood in order to produce relatively shorter individuals and ultimately promote healthy aging in our societies?…”
mentioning
confidence: 99%